Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0131959
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health in Cleaners in Northern Europe: Is Susceptibility Established in Early Life?

Abstract: RationaleThere is some evidence that maternal smoking increases susceptibility to personal smoking’s detrimental effects. One might question whether early life disadvantage might influence susceptibility to occupational exposure.ObjectivesIn this cross-sectional study we investigated respiratory symptoms, asthma and self-reported chronic obstructive pulmonary disease (COPD) as related to working as a cleaner in Northern European populations, and whether early life factors influenced susceptibility to occupatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 32 publications
(33 reference statements)
1
35
0
2
Order By: Relevance
“…Long-term exposure to the occupational agent (eg, in persons who start work at a very young age and/or cannot change their workplace when the symptoms start) could play a role. For instance, a crosssectional study performed in 13 499 cleaners in Northern Europe investigated whether early life factors influenced susceptibility to the unhealthy effects of occupational cleaning [93]. Associations with respiratory symptoms, asthma, and self-reported COPD were analyzed with multiple logistic regression adjusted for sex, age, smoking, educational level, parents' educational level, body mass index, and participating center.…”
Section: Occupational Agentsmentioning
confidence: 99%
“…Long-term exposure to the occupational agent (eg, in persons who start work at a very young age and/or cannot change their workplace when the symptoms start) could play a role. For instance, a crosssectional study performed in 13 499 cleaners in Northern Europe investigated whether early life factors influenced susceptibility to the unhealthy effects of occupational cleaning [93]. Associations with respiratory symptoms, asthma, and self-reported COPD were analyzed with multiple logistic regression adjusted for sex, age, smoking, educational level, parents' educational level, body mass index, and participating center.…”
Section: Occupational Agentsmentioning
confidence: 99%
“…Early life factors, in particular parental smoking, have been hypothesized to play a role for modifying susceptibility. [ 26 28 ]. No previous study on early life factors has yet followed participants into old age or had the power to investigate individual early life factors in sufficient detail.…”
Section: Introductionmentioning
confidence: 99%
“…This result was in agreement with the study conducted in Iran [11], which depicted higher prevalence of breathlessness of exposed groups than controls with a significant p-value. Another study in Northern Europe [12] also found that respiratory symptoms and disease were more common among cleaners.…”
Section: Discussionmentioning
confidence: 87%